What platform makes students enjoy the learning during covid-19 pandemic? - Maya Oktaviani; Vania Zulfa; Elmanora Elmanora (Universitas Muhammadiyah Surabaya, 2020)
Abstract. Covid-19, which is pandemic throughout the world, including Indonesia, forcedface-to-face learning to be transformed into distance learning. Distance learning done through various platforms. This research aims to find out what platform was the most enjoyable to use during learning for students. The sample were 119 students from the Family Welfare Education Study Program, Engineering Faculty, Universitas Negeri Jakarta. The study conducted from April to May 2020. The research used descriptive qualitative methods. The results showed that 45% of students chose Google Classroom as the most enjoyable platform to use during distance learning, 28% of students chose Zoom, 9% of students chose WhatsApp, and the rest chose on several platforms such as Edmodo, Slido, Quizizz, Schoology, Seesaw, and Google Meet. The main reason for choosing the platform as seen from the effectiveness and ease of access. To keep distance learning enjoyable for students, they create coping strategies for themselves. Respondents did somethings such as journaling, always thinking positively, interacting with friends and family, creating an atmosphere of learning like being in class, and not delaying assignments. When there is free time, they often listen to music, watch movies, play with pets,or get more rest.Â Keyword: distance learning,joyful learning, enjoyable platform used, coping strategies